Policy on the Frontlines: Community Nonprofit Organizations Working with Older Adults During COVID-19 in Montréal - Joy, Meghan; Fournier, Laurie; Marr-Laing, Kate; Hebblethwaite, Shannon (Canadian Journal of Nonprofit and Social Economy Research / Revue canadienne de recherche sur les OSBL et l’économie sociale, 2025)
Community nonprofit organizations (CNPOs) are a vital component of the social infrastructure that addresses the needs of older adults aging in place. Despite this, CNPOs are overlooked in political research and relevant policies, such as the age-friendly cities program. This article examines CNPO work during the COVID-19 pandemic in Montréal, Québec. Policy analysis, surveys, and interviews with CNPO staff, local policy actors, and older adults reveal that CNPOs became increasingly essential frontline social service providers during the pandemic. While CNPOs fill gaps in public and private social infrastructures, they are facing considerable service, labour, administrative, and financial challenges due to inadequate policy support. Policy on aging must incorporate CNPO work in different sectors and communities, facilitate partnerships that respect CNPO autonomy, and improve CNPO funding.